Nursing care in post cesarean patient with severe preeclampsia in the gynecobstetrics service of the national hospital of Cajamarca 2022 - Cotrina Celiz , Eresvita; Villanueva Julcamoro, Maritza Mercedes; Vivanco Hilario, Sofía Dora (SCT Proceedings in Interdisciplinary Insights and Innovations, 2025)
Introduction: Preeclampsia is characterized by hypertensive disorders from the 20th week of gestation, with high possibility of eclampsia until the immediate puerperium, also proteinuria and edema are present. Objective: To determine the role of nursing in the care of post cesarean patient with severe preeclampsia. Methods: The study has a qualitative approach, single case type, applying the nursing care process to a 27-year-old patient selected by convenience; the data collection instrument was the assessment guide according to the eleven functional patterns of Maryory Gordon. Results: Seven altered nursing diagnoses were recognized, prioritizing as the main nursing diagnosis (00132) acute pain r/physical injury agent evidenced by facial expression of pain, expressive behavior and VAS 6/10, and as a collaborative problem the risk of complication: hypovolemic shock. Conclusion: The clinical characteristics and the risks of complication in the patient with severe preeclampsia were assessed and identified, individualized nursing interventions were planned which had favorable results in the evolution of the patient, +1, +1. +1 and +1, the nursing care process based on its five stages was applied, managing to provide comprehensive care with quality that allowed obtaining favorable results in the recovery of the patient’s health